STUDY ON EFFECTIVE NOISE BARRIER AT SENIOR HIGH SCHOOL (SMAN 02) CIBINONG - Aulia Ramandha; Wisnu Eka Yulyanto; Sandra Madonna (Universitas Trisakti, 2019)
Aim: The aim of this study is to design noise barrier shapes and to investigate its effectiveness in reducing traffic noise at one public school in Indonesia. Methodology and Results: Two types of barriers were designed on a laboratory scale using plywood materials and the noise level was measured using Noise Analyzer Briiel and Kjaer Type 2250. Noise reduction was analyzed by using the Insertion Loss method based on the difference of the noise level before and after implementing the barrier. The results show that the barrier Type II with a length of 200 cm, a receiver height of 30 cm, and a curved shape of 45° angle (Type L) is more effective in reducing the noise than the other variation of barrier shape and length. Barrier Type L (Type II) can reduce the noise at high frequency between 1–8 kHz with an Insertion Loss value of 6.9–27.9 dB. Conclusion, significance and impact study: The noise barrier Type II, with specifications of 20 m length, 3 m height, and barrier material of reinforced concrete, is recommended to be used at the high school to reduce the road traffic noise.